Assessing distributive inequities in FEMA's Disaster recovery assistance fund allocation. (May 2022) - Emrich, Christopher T.; Aksha, Sanam K.; Zhou, Yao
Abstract: Social vulnerability is significant in differential disaster impacts and outcomes and has been shown to influence the pace and progression of post-disaster recovery processes. Various disaster assistance programs - designed to support individual survivors, states, local governments, non-governmental entities, and businesses - may be distributing funds inequitably because they are not accounting for social vulnerabilities. One such program, the Federal Emergency Management Agency's Individuals and Households Program (IHP) program supports homeowners and renters for rental, repair, replacement, and permanent housing construction of disaster-damaged houses as well as providing other needs assistance to disaster victims with disaster-related non-housing expenses. To date, limited exploration connecting underlying social vulnerabilities and distribution of federal disaster assistance funds has provided only an incomplete understanding of the connections between underlying socio-economic conditions and often inequitable federal recovery assistance distribution. We analyzed county-level IHP assistance provided to homeowners between 2010 and 2018 and explored the relationships between fund distribution and social vulnerability indicators while controlling for total damages. Employing ordinary least squares regression analysis, we assessed links between Total Assistance, Housing Repair/Replace Assistance and Other Needs Assistance against social vulnerability variables from the Social Vulnerability Index (SoVI) framework. Results highlight specific social vulnerability variables influencing FEMA's distribution of disaster recovery assistance with race/ethnicity-related variables as the most frequent (regularly negative) influence on recovery fund receipt. Findings suggest that disaster assistance receipt is linked to underlying social vulnerability. As such, greater attention to and inclusion of social vulnerabilities would lead to more equitable distribution of disaster recovery funds. Highlights: County level social indicators predict disaster recovery funds allocations when controlling for damages. A county's racial and ethnic makeup forecasts inequities in FEMA's IHP program recovery fund delivery. Although less influential than race/ethnicity, socio-economic factors also drive inequity in FEMA's IHP fund distribution. Rawlsian equity measures help provide a more robust understanding of disaster equity challenges than statistics alone. FEMA's IHP program recovery fund distribution is not 100% inequitable. Several instances of equitable funding exist.